The Factors affecting household e-waste management behavior Thung Khai Subdistrict, Don Ta Khao District, Trang Province, Thailand - Somsiri Decharat; Thanawan Buacharoen; Jarawee Munwean; Sathiya Phengratsami (YCAB Publisher, 2026)
Background: Rapid technological advancement has changed consumer behavior, increasing demand for electronic devices, which are now essential in daily life. Objectives: To study the knowledge, attitudes, behaviors, and the factors influencing the related to electronic waste management of households. Methods: This cross-sectional descriptive study was conducted among households with 344 participants. A random sampling method was then used to select households from among those residing in Thung Khai Subdistrict, Yan Ta Khao District, Trang Province, Southern Thailand, between September 2024 to March 2025. The study questionnaire was given to the 344 participants. Descriptive statistics and chi-square test were used to analyze. Results: Overall mean knowledge score of 11.28 (SD = 2.58), corresponding to the “moderate” category. The aggregate attitude score (M = 3.81, SD = 1.58), placing them in the “high” attitudinal category, and the overall mean behavior score of 2.14 (SD = 0.74), corresponding to a “fair” level of practice. Only prior exposure to information on electronic waste management demonstrated a statistically significant association with respondents’ self‐reported e‐waste behaviors (χ² = 17.89, p = .01). Conclusions: Thus, effective e-waste management is crucial for achieving sustainable development goals and requires collaboration across all sectors. Raising public awareness of circular economy principles is vital for enhancing community engagement in e-waste management. Keywords: Factors affecting; household e-waste management; behavior; Trang Province